Synthesis and Characterization of Self-Healing Polymers Obtained from Polyphenols and Cyclic Carbonates of Amide Derivative of Macaw Palm Oil - Alarcon, Rafael Turra; Gaglieri, Caroline [UNESP]; de Freitas, Jonatha; Bannach, Gilbert [UNESP]; Cavalheiro, Éder Tadeu Gomes (My University, 2025)
In this work, the Brazilian biomass – macaw palm oil, was reacted with tris(2-aminoethyl)amine to give a fatty amide derivative, which was further modified to obtain an epoxidised derivative. After that, the last derivative reacted with CO2, providing a new carbonated compound. The vegetable oil-based products were analysed using spectroscopic techniques and showed fluorescence when exposed to UV light. The carbonated compound was polymerised with four different polyphenols (quercetin, curcumin, tannic acid, and gallic acid). This resulted in dark brown, thermosetting poly-hydroxycarbonates with a shiny and brittle appearance. Modified vegetable oil compounds and final polymers present bio-based and bio-based carbon contents above 88%, indicating their renewability. Polymers made with quercetin and gallic acid were hydrophobic (water-repellent). Thermal analysis confirmed that all polymers could withstand temperatures up to 195 °C before decomposing. In addition, they have resistance against acid solutions but are fully hydrolysed after 24 h in an alkaline solution. These new polymeric materials also present self-healing properties; therefore, they can be healed and recovered by simple heating using a red-light LED (660 nm) and hydraulic press, a greener, faster, and more straightforward method.
Keywords: Bio-Based Polymers; Biomass; Green Chemistry; Self-healing